Probittacomorpha brisaci n. sp. (Ptychopteridae, Bittacomorphinae) from the Late Miocene of Montagne d’Andance, Saint Bauzile, Ardèche (France) - Krzeminski, Wiesław; Kania, Iwona; Nel, André (Zootaxa, 2012)
A new species of phantom crane flies (Ptychopteridae: Bittacomorphinae), Probittacomorpha brisaci n. sp., is described based on a single specimen from the Late Miocene volcano-sedimentary paleolake of Montagne d’Andance (Saint Bauzile, Ardèche, France). This is the second known species of the fossil genus Probittacomorpha. Previously described species has been found in the Paleocene-Eocene Fur-Formation (Moler) of Denmark.